Implementation of the National Song in the Forming of Religious Character and Nationalism in Class IV Students in SD Negeri Cilame - Kurniasih, Siti (Universitas Muhammadiyah Surakarta, 2022)
Planting a National Song in the Formation of Religious Character and Nationalism in Grade IV Students at SD Negeri Cilame, aims to shape the character of students, especially in religious and nationalist characters through national songs, therefore in shaping the character of students can be done in various ways, one of which is by getting used to sing the national anthem to students, so that little by little students will apply the moral messages contained in the song to everyday life, so that students become better individuals and have character. This study used a qualitative descriptive method, data collection techniques were carried out by observation, interviews, and documentation studies. The results showed that the fourth grade students of SD Negeri Cilame carried out the planting of the national song in character building in learning. Like before and after learning all students sing the compulsory song.